REVIEW ARTICLE FORMULASI PEMBUATAN MINUMAN ISOTONIK BERBAHAN BAKU AIR NIRA POHON AREN (Arenga pennata MERR.) DAN SARI BUAH BELIMBING WULUH (Averrhoa bilimbi L.) - An Nisaa Nurzak (Jurnal Medika Hutama, 2021)
Isotonic beverages are defined as carbohydrate-containing beverages with a concentration of 6-9% b/v and contain small amounts of minerals, such as sodium, potassium, chloride, posfat and fruit flavor. The quality requirements of isotonic beverages in Indonesia refer to SNI 01-4452-1998. Nira Aren can be processed into fresh, packaged beverages (a type of isotonic drink on the market). Water is very easily damaged due to contamination by Acetobacter sp microorganisms. so that the nutritional content in it also changes. Therefore, the addition of Averrhoa bilimbi L Belimbing wuluh with a high nutritional value content into the formulation made. The preparation of this Scientific Paper uses secondary data with library study methods or literature studies from several official and trusted journals and then combined and drawn conclusions. From the study the literature obtained that water with the addition of Averrhoa bilimbi L can be formulated into isotonic drinks that conform to the quality standards of isotonic drinks that have been established.